Reduction of electron-deficient pyrroles using group I and II metals in ammonia - Donohoe, T; Guyo, P; Beddoes, R; Helliwell, M (1998)
The preparation and Birch reduction of a series of electron-deficient pyrroles is described. This methodology allows the synthesis of a variety of C-2 substituted 3-pyrrolines in good to excellent yields. The role of various activating groups (amide, ester, carbamate and urea) has been examined with regard to both stability under the Birch conditions and ease of deprotection after reduction. In addition, we discovered that the 3-pyrroline skeleton can be oxidised at C-5 with chromium trioxide-3,5-dimethylpyrazole to form the 3-pyrrolin-2-one nucleus. The identity of the Birch reduced products and also of the oxidised 3-pyrrolin-2-ones has been confirmed by X-ray crystallography on two derivatives.